Cavitation Analysis of Kaplan-Series Propeller: Effect of Pitch Ratio and nProp using CFD - Mohammad Danil Arifin; Frengki Mohamad Felayati (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Cavitation is defined as a phenomenon or action of the traveling bubbles that pass through the hydrofoil in which the reduction of pressure below the liquid’s vapor pressure leads to the formation of small vapor bubbles (or cavities) caused by the dynamic pressure of the propeller blades. It caused some effects on the propeller of the ship i.e. it can greatly reduce a ship’s propelling efficiency, damaged propeller material or blade erosion, vibration, and disturbance noises. Cavitation can be minimized by proper attention regarding the design of the propellers and variation of propeller variables parameters. For that reason, this research conducts a cavitation analysis on the Kaplan-Series of the CPP by varying P/Db=0.4, P/Db=0.6, and P/Db=0.8; also the rotational speed of the propeller (nProp) i.e. 125 rpm, 175 rpm and, 225 rpm. The numerical analysis was made based on the Computational Fluid Dynamic Method (CFD) to calculate the pressure ratio (deltaP) and percentages of the cavitation area (Rs) due to a configuration of the propellers parameter. The simulation consists of the 3 steps; pre-processor, solver manager, and post-processor. The result shows that the value of the pressure ratio increased significantly at the higher P/Db and nProp. Also, the variation of P/Db and nProp has a significant effect on the development of Rs (%) at the higher P/Db and nProp.